PENGARUH FINANCIAL LITERACY DAN DIGITAL LITERACY TERHADAP FINANCIAL RESILIENCE DENGAN FINANCIAL BEHAVIOR SEBAGAI MEDIASI PADA YAYASAN PENDIDIKAN BAITURRAHMAH PADANG - Dina Patrisia; Yoga Firman (Smart Education, 2026)
Abstract: This study aims to analyze the influence of financial literacy and digital financial literacy on financial resilience with financial behavior as a mediating variable in employees of the Baiturrahmah Padang Education Foundation. Financial resilience is an important issue in facing economic uncertainty and the increasingly rapid development of digital technology. Financial literacy and digital literacy are believed to be able to improve individuals' ability to manage finances and form better financial behaviors that can improve financial resilience. This study uses a quantitative approach with a causative research type. The population in this study were 505 employees of the Baiturrahmah Padang Education Foundation with a sample of 223 respondents determined using the proportional cluster random sampling technique. Data were collected through questionnaires distributed online using Google Forms and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study indicate that financial literacy does not directly influence financial resilience, but has a positive and significant effect on financial behavior. Digital financial literacy does not directly influence financial resilience, but has a positive and significant effect on financial behavior. Furthermore, financial behavior has a positive and significant effect on financial resilience. Furthermore, financial behavior has been shown to mediate the relationship between financial literacy and digital financial literacy on financial resilience. This study concludes that improving employee financial resilience can be achieved through improving financial literacy and digital literacy, followed by the development of good financial behavior Keywords: Financial Literacy, Digital Financial Literacy, Financial Behavior, Financial Resilience Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh financial literacy dan digital financial literacy terhadap financial resilience dengan financial behavior sebagai variabel mediasi pada pegawai Yayasan Pendidikan Baiturrahmah Padang. Ketahanan keuangan menjadi isu penting dalam menghadapi ketidakpastian ekonomi dan perkembangan teknologi digital yang semakin pesat. Literasi keuangan dan literasi digital diyakini mampu meningkatkan kemampuan individu dalam mengelola keuangan serta membentuk perilaku keuangan yang lebih baik sehingga dapat meningkatkan ketahanan finansial. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian kausatif. Populasi dalam penelitian ini adalah pegawai Yayasan Pendidikan Baiturrahmah Padang sebanyak 505 orang dengan jumlah sampel 223 responden yang ditentukan menggunakan teknik proportional cluster random sampling. Data dikumpulkan melalui kuesioner yang disebarkan secara online menggunakan Google Form dan dianalisis menggunakan Structural Equation Modeling (SEM) berbasis Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa financial literacy tidak berpengaruh langsung terhadap financial resilience, namun berpengaruh positif dan signifikan terhadap financial behavior. Digital financial literacy tidak berpengaruh langsung terhadap financial resilience, tetapi berpengaruh positif dan signifikan terhadap financial behavior. Selanjutnya, financial behavior berpengaruh positif dan signifikan terhadap financial resilience. Selain itu, financial behavior terbukti mampu memediasi hubungan antara financial literacy dan digital financial literacy terhadap financial resilience. Penelitian ini menyimpulkan bahwa peningkatan ketahanan keuangan pegawai dapat dilakukan melalui peningkatan literasi keuangan dan literasi digital yang diikuti dengan pembentukan perilaku keuangan yang baik. Kata Kunci: Literasi Keuangan, Literasi Keuangan Digital, Perilaku Keuangan, Ketahanan Keuangan